Constructing Black People in The Clansman Novel by Thomas Dixon (A Postcolonial Study) - Elis Elda Sari; Rahmawati Azi (ELITE: Journal of English Language and Literature, 2019)
This study aims to analyze the construction of the black people in The Clansman novel written by Thomas Dixon. This study used a postcolonial perspective that is orientalism proposed by Edward Said. Orientalism that tried to see how the west constructs the east in stereotypical images is adapted to how racist America constructs black. This study combines library and media research by applying a descriptive qualitative method in analyzing the data. The data collected through the process of re-reading and classifying the data. This study found that the construction of black people in the Clansman novel is built in racist ideology. The author of the novel represents the white Ku Klux Klan to created the binary opposition of black as inferior and white as superior ones in the aspects of physical, mental, and intellectual. White is represented as a perfect creature because of their appearance, behavior, and also knowledge, while black represented as savage and brute, black-skinned as the symbol of ugliness, and having an intellectual deficiency. However, the construction of black in this novel is not regardless of the author’s world view about racism in the United States.